Cleanup of sewage sludge spiked with Cd, Cu, and Zn: Sludge quality and distribution of metals in the "soil-plant-water" system. (March 2021) - Barraoui, Driss; Blais, Jean-François; Labrecque, Michel
Abstract: Corn was grown under greenhouse conditions in the presence of uncleaned versus cleaned municipal sewage sludge to assess the effectiveness of a chemical leaching process that uses an inorganic acid and strong oxidants to clean biosolids (i.e., to remove metals without reducing their agronomic potential). Specifically, our study analyzed physicochemical sludge from the Montreal (MSL) wastewater treatment plant (WTP) and biological sludge from the Becancour (BSL) WTP. Both biosolids were spiked with individual metals (dry weight basis): Cd (100 mg kg-1), Cu (3000 mg kg −1 ), and Zn (5000 mg kg −1 ), or their mixture. MSL biosolid enrichment led to the solubilization of added metals and removed 84–88% of Cd, 78–79% of Cu, and 79–81% of Zn. Similarly, BSL biosolid enrichment resulted in the removal of 86–88% of Cd, 80–81% of Cu, and 88–89% of Zn. The fractional distribution of metals varied between biosolids depending on their production process, stabilization, and initial metal concentration. In the MSL biosolids, only Cu partitioning was influenced by spiking, cleanup, and washing. The three metals (Cd, Cu, and Zn) occurred either in their crystalline phase or were linked to Fe oxide, organic matter, or carbonate. In the BSL biosolids, the metals that were not in their crystalline phase were only associated with Fe oxide. This study demonstrated that 99% of Cd and Cu and 97% of Zn contents remained in the soil; however, biosolid cleanup generally decreased metal concentrations in plants, leachate, and/or soil. Graphical abstract: Image 1 Highlights: Sludge-borne metals added to a soil redistribute and become fixed as native elements. Even highly loaded, sludge can be satisfactory decontamined to be used in agriculture. METIX-AC process reduces environmental and health risks due to sludge-borne metals. Sludge decontamination by METIX-AC is a promising way for a sustainable agriculture.